DRUG UTILIZATION STUDY ON ORAL HYPOGLYCEMIC AGENTS IN TYPE 2 DIABETIC PATIENTS OF TERTIARY CARE HOSPITAL - BHUVANESWARI, SARAGADAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the study is to determine the patient demographic characteristics, inspect prescription patterns of oral hypoglycemic agents, distribution of comorbid conditions in the outpatient department (OPD) of Visakha Institute of Medical Sciences (VIMS), Visakhapatnam. Method: A prospective observational study was conducted in patients with established type 2 diabetes mellitus (n=185) visiting OPD which were interviewed using a structured questionnaire during the period September– December 2019. Results: Majority of the type 2 diabetic patients in VIMS were treated with double drug therapy. The most commonly prescribed class of oral hypoglycemic agents were biguanides (metformin) followed by sulfonylureas (glimepiride), thiazolidinediones (pioglitazone), alpha-glucosidase inhibitor (voglibose), and dipeptidyl peptidase-4 inhibitor (vildagliptin).